On comparing permeation through Matrimid®-based mixed matrix and multilayer sandwich FAU membranes: H2/CO2 separation, support functionalization and ion exchange. (5th January 2017) - Mundstock, Alexander; Friebe, Sebastian; Caro, Jürgen
Abstract: A series of supported membranes with zeolite FAU either as a thin layer or as powder in Matrimid as Mixed Matrix Membrane (MMM) have been prepared and evaluated in the H2 /CO2 separation. In addition to neat NaX membrane layers, we developed two novel composite materials, namely FAU/Matrimid ® Mixed Matrix Membranes (MMMs) as well as NaX/Matrimid ® multilayer/sandwich membranes, all of them supported by porous alumina plates. The influence of different pre-synthetic support modifications (APTES = 3-aminopropyltrietoxysilane, PDA = polydopamine) on the quality of neat supported NaX membranes grown as layer on these modified supports has been investigated studying the H2 /CO2 separation performance. It could be shown that NaX membrane layers grown on modified supports show an remarkably increased quality and correspondingly higher H2 /CO2 separation factors α (H2 /CO2 ) (α = 8.0 for neat NaX, α = 8.9 for NaX/APTES and α = 10.3 for NaX/PDA). In the preparation of MMMs, the separation performance could be improved by ion exchanged Na-FAU powders. Exchanging the Na + of the as-synthesized NaX particles for metal ions with higher ionic potentials like Co 2+, results in enhanced mixed gas separation factors α in the H2 /CO2 separation (NaX/Matrimid ® MMM α = 4.0 and CoX/Matrimid ® MMM α = 5.6). Graphical abstract: Highlights: Supported NaX membrane layers are evaluated in H2 /CO2 separation. Support modification is decisive for separation performance. Cation-exchanged FAU powder is used as filler in Mixed Matrix Membranes (MMMs). Substituting Na + by two-valence ions like Co 2+ in MMMs increases H2 /CO2 separability.